Analisis Pengelolaan Tempe Dalam Perspektif Etika Bisnis Islam Dalam Pengembangan Usaha Umkm Pada Pabrik Tempe Sofyan - Zainarti; Husnul Khatimah; Dinda Dewi Rahma Wijaya (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
One of the typical foods from Indonesia is tempeh, tempeh is a food that comes from fermented soybeans. There are many advantages of tempeh, some of these advantages are that the price of tempeh is very affordable, it is rich in nutritional value, it can be processed into various types of food, apart from being a side dish, it can also be processed. as a snack, therefore home businesses that produce tempeh have a great opportunity to compete in the business market, especially in terms of food. The development of micro, small and medium enterprises in tempeh production is the main focus in the perspective of Islamic business ethics. This research uses a qualitative approach to explore Islamic ethical values applied in the management of Tempe . The findings highlight the processing process, obstacles in business development, honesty of business owners in developing tempe businesses in business practices. The integration of these principles can strengthen the sustainability of business, improve worker welfare, and provide benefits to society at large. The results provide insight into how an ethical approach to business can improve the performance of business in the food industry, especially in tempe production, as well as providing a basis for further discussion regarding the role of Islamic business ethics in the development of business.